The Influence of the Principal's Example on Teachers' Discipline and Work Motivation at SMPN 5 Mandau - Fatmawati, Fatmawati; Adityawarman, Adityawarman; Samsurijal, Samsurijal (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the principal's exemplary behavior on the discipline and work motivation of teachers at SMPN 5 Mandau. The method used in this study is quantitative with a regression approach. The population in this study were teachers at SMPN 5 Mandau, with a sample of 20 teachers. Data collection techniques were carried out through questionnaires, observations and documentation. The research instruments were in the form of questionnaires and observation sheets that had been validated. The data analysis technique used simple linear regression and t-test to determine the effect between variables. The results showed that the principal's exemplary behavior had a positive effect on discipline with a Tcount value (5.730) Ttable (2.097) and a significance of 0.001 0.05 so that H0 was rejected and H1 was accepted. The principal's exemplary behavior had a positive effect on teacher work motivation with a Tcount value (2.309) Ttable (2.097) and a significance of 0.004 0.05 so that H0 was rejected and H1 was accepted. So it can be concluded that Ho is rejected and H1 is accepted so that there is a significant influence between the principal's exemplary behavior on teacher discipline and work motivation at SMPN 5 Mandau.